2023
DOI: 10.3389/fphar.2023.1185850
|View full text |Cite
|
Sign up to set email alerts
|

Role of endogenous and exogenous antioxidants in risk of six cancers: evidence from the Mendelian randomization study

Abstract: Background: Although oxidative stress is known to contribute to cancer, and endogenous and exogenous antioxidants are thought to prevent tumorigenesis by suppressing oxidative stress-induced DNA damage, antioxidants have also been reported to show negative effects on tumor formation, necessitating characterization of the causal associations between antioxidants and cancer risk.Methods: In this study, Mendelian randomization (MR) analysis, primarily inverse-variance weighted MR, was used to assess the causal ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…Oxidative stress is a critical contributor to the pathogenesis of different chronic diseases (Kiran et al, 2023;Husain et al, 2023). The exogenous intake of antioxidants as a dietary supplement can decrease oxidative damage (Bouayed and Bohn, 2010;Zhu et al, 2023). Besides plants' flavonoids, phenolics and other phytoconstituents have been reported to exert numerous biological activities, including anti-tumour, antiinflammatory, and antioxidant actions (Gauri et al, 2016;Ullah et al, 2020;Bagchi, 2021;Ghosh et al, 2022;Acharya et al, 2022a, b;Bee et al, 2023;Jakkana and Yamala, 2024).…”
Section: Introductionmentioning
confidence: 99%
“…Oxidative stress is a critical contributor to the pathogenesis of different chronic diseases (Kiran et al, 2023;Husain et al, 2023). The exogenous intake of antioxidants as a dietary supplement can decrease oxidative damage (Bouayed and Bohn, 2010;Zhu et al, 2023). Besides plants' flavonoids, phenolics and other phytoconstituents have been reported to exert numerous biological activities, including anti-tumour, antiinflammatory, and antioxidant actions (Gauri et al, 2016;Ullah et al, 2020;Bagchi, 2021;Ghosh et al, 2022;Acharya et al, 2022a, b;Bee et al, 2023;Jakkana and Yamala, 2024).…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, Mendelian randomization (MR) is a powerful analytical method that uses genetic variation to study the causal impacts of risk factors on traits ( Lawlor et al, 2008 ; Evans and Davey Smith, 2015 ; Burgess et al, 2019 ). Previous research using MR analysis has suggested possible causal links between levels of circulating antioxidants and a range of health conditions ( Ni et al, 2023 ; Tang et al, 2023 ; Zhu et al, 2023 ; Chen et al, 2024 ; Zou et al, 2024 ). The primary objective of this study was to investigate the causal connection between diet-derived circulating antioxidants and the risk of OP.…”
Section: Introductionmentioning
confidence: 99%